The Correlation Between Workload And Ergonomic Position With The Incidence Of Low Back Pain In Nurses At Pringsewu Regional Public Hospital - Novita Putri Hardiyati; Rizki Yeni Wulandari; Yunina Elasari; Ardinata Ardinata (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: To determine the